Optimization of oil removal by sugarcane bagasse using response surface methodology - Asilah Ahmad Samsuir; Norhisyam Ismail; Rozidaini Mohd Ghazi (Universiti Malaysia Kelantan, 2016)
Oily wastewater is one of the environmental concerns nowadays. The seriousness of oil pollution problem comes in sync with the expansion of oil exploration and production activities, as well as industrial growth around the world. In this study, the ability of sugarcane bagasse in removing oil in synthetic oil wastewater was investigated. Parameters affecting oil removal such as concentrations of synthetic oil wastewater, biosorbent dosage and contact time were optimized using Response Surface Methodology (RSM) via Box Behnken Design. Sugarcane bagasse showed excellent efficiency in removing oil with percentage removal up to 98.73% at 1.3 h contact time with 3.06 g of biosorbent dosage and 16.9% of synthetic oil wastewater concentration. The use of sugarcane bagasse in removing oil in water was successfully prove in this study.